Pachydermoperiostosis mimicking acromegaly: A case report - Prerna; Romana Ghosh; Jayanta K Barua; Arup K Das (Wolters Kluwer Medknow Publications, 2018)
Pachydermoperiostosis is a rare, hereditary disease commonly presenting with digital clubbing, pachyderma, and periosteal hypertrophy. Coarsening of facial features and spade-like enlargement of hands and feet may give rise to a diagnostic dilemma between pachydermoperiostosis and acromegaly. This report highlights a case of a 36-year-old man who presented with broadening of hands and feet, facial skin thickening, and edematous and drooping eyelids for the last 10 years.There was no history of similar presentation in his family. Such clinical presentation in corroboration with normal growth hormone level and prominent radiological abnormalities prompted us to make a diagnosis of pachydermoperiostosis.